Building a better neonatal mouse model to understand infant respiratory syncytial virus disease. Issue 1 (December 2015) - You, Dahui; Siefker, David; Shrestha, Bishwas; Saravia, Jordy; Cormier, Stephania
Abstract Background Respiratory syncytial virus (RSV) is the number one cause of lower respiratory tract infection in infants; and severe RSV infection in infants is associated with asthma development. Today, there are still no vaccines or specific antiviral therapies against RSV. The mechanisms of RSV pathogenesis in infants remain elusive. This is partly due to the fact that the largely-used mouse model is semi-permissive for RSV. The present study sought to determine if a better neonatal mouse model of RSV infection could be obtained using a chimeric virus in which the F protein of A2 strain was replaced with the F protein from the line 19 clinical isolate (rA2-19F). Methods Five-day-old pups were infected with the standard laboratory strain A2 or rA2-19F and various immunological and pathophysiological parameters were measured at different time points post infection, including lung histology, bronchoalveolar lavage fluid (BALF) cellularity and cytokines, pulmonary T cell profile, and lung viral load. A cohort of infected neonates were allowed to mature to adulthood and reinfected. Pulmonary function, BALF cellularity and cytokines, and T cell profiles were measured at 6 days post reinfection. Results The rA2-19F strain in neonatal mice caused substantial lung pathology including interstitial inflammation and airway mucus production, while A2 caused minimal inflammation and mucus production. Pulmonary inflammation was characterized by enhanced Th2 and reduced Th1 and effector CD8+ T cells compared to A2. As with primary infection, reinfection with rA2-19F induced similar but exaggerated Th2 and reduced Th1 and effector CD8+ T cell responses. These immune responses were associated with increased airway hyperreactivity, mucus hyperproduction and eosinophilia that was greater than that observed with A2 reinfection. Pulmonary viral load during primary infection was higher with rA2-19F than A2. Conclusions Therefore, rA2-19F caused enhanced lung pathology and Th2 and reduced effector CD8+ T cell responses compared to A2 during initial infection in neonatal mice and these responses were exacerbated upon reinfection. The exact mechanism is unknown but appears to be associated with increased pulmonary viral load in rA2-19F vs. A2 infected neonatal lungs. The rA2-19F strain represents a better neonatal mouse model of RSV infection.